اعتماد معايير محاسبة التكاليف لدول مختارة لمعالجة مشكلات النظام المحاسبي الموحد الجانب الكلفوي (Journal of Accounting and Financial Studies ( JAFS ), 2020)
You need all economic units to the analytical and detailed information to make different decisions, and should be characterized by this information to relevance and credibility and to provide in a timely manner, and provide cost information to be used for the purposes of financial accounting system (to determine the cost of inventory types, the cost of production) For the purposes of management accounting to take a different decisions (pricing decision, to accept or reject the order), and faces many problems cost accounting system in addition to the failure to address many aspects of it should be developed to take advantage of the current system of cost accounting for the countries selected criteria.